Recovery of impaired endogenous pain modulation by dopaminergic medication in Parkinson's disease - Florin, Esther; Koschmieder, Kim Caroline; Schnitzler, Alfons; Becker, Susanne (Movement disorders, 2020)
Background Of patients with Parkinson's disease (PD), 30% to 85% report pain. However, mechanisms underlying this pain remain unclear. In line with known neuroanatomical impairments, we hypothesized that pain in PD is caused by alterations in emotional-motivational as opposed to sensory-discriminative pain processing and that dopamine recovers the capacity for endogenous emotional-motivational pain modulation in patients with PD. Methods A total of 20 patients with PD played a random reward paradigm with painful heat stimuli in addition to assessments of pain sensitivity once with and once without levodopa. Results Levodopa increased endogenous pain inhibition in terms of perceived pain intensity and un/pleasantness compared with a medication off state. Higher clinical pain was associated with higher increases in pain inhibition. Levodopa did not affect heat pain threshold, tolerance, or temporal summation. Conclusion Patients with PD seem to be predominately impaired in emotional-motivational as opposed to sensory-discriminative pain processing. A differential understanding of pain in PD is urgently needed because effective treatment strategies are lacking. © 2020 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society